Participation of Primary School Teachers in Educational Innovations as the Groundwork for Their Professional Development: Organization and Management; Advances in Intelligent Systems and Computing; Vol. 677 : Linguistic and Cultural Studies: Traditions and Innovations, (LKTI 2017) - Pozdeeva S. I. Svetlana Ivanovna (Lifelong Learning, 2017)
Title screen